2003
DOI: 10.1002/dvdy.10485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of neural crest cell death, migration, and function during vertebrate embryogenesis

Abstract: Cranial neural crest cells are a multipotent, migratory population that generates most of the cartilage, bone, connective tissue and peripheral nervous system in the vertebrate head. Proper neural crest cell patterning is essential for normal craniofacial morphogenesis and is highly conserved among vertebrates. Neural crest cell patterning is intimately connected to the early segmentation of the neural tube, such that neural crest cells migrate in discrete segregated streams. Recent advances in live embryo ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 69 publications
0
78
0
Order By: Relevance
“…To establish which molecules regulate the pmx in L. violacea and L. portoricensis, we examined the expression of other skeletogenic factors known to control avian craniofacial development (18)(19)(20)(21). We found that in these two species, early in development Bmp4 is primarily expressed in domains coinciding with their developing pmx (compare the bone condensation in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To establish which molecules regulate the pmx in L. violacea and L. portoricensis, we examined the expression of other skeletogenic factors known to control avian craniofacial development (18)(19)(20)(21). We found that in these two species, early in development Bmp4 is primarily expressed in domains coinciding with their developing pmx (compare the bone condensation in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the level of the hindbrain, the pattern of neural crest migration reflects the segmentation of the neural tube into rhombomeres, such that hindbrain neural crest cells move in distinct streams emanating from r2, 4, and 6. These streams form from a combination of reduced neural crest production and an environment inhibitory to neural crest migration at axial levels devoid of neural crest (Kulesa et al, 2004). The molecular cascade of events that restricts neural crest migration through the cranial mesenchyme remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…At hindbrain levels, neural crest cell migration is segmented into three distinct streams adjacent to rhombomere 2 (r2), r4 and r6, with no neural crest cells apparent adjacent to r3 and r5. Cranial neural crest streams form from a combination of reduced neural crest production from r3 and r5 (reviewed in Kulesa et al, 2004) and an environment inhibitory to neural crest migration in the adjacent mesenchyme (Farlie et al, 1999;Trainor et al, 2002;Kulesa et al, 2004). Those cells originating in r3 and r5 deviate rostrally or caudally and fail to enter the adjacent preotic mesoderm or otic vesicle region (Sechrist et al, 1993;Kulesa and Fraser, 2000;Trainor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because most of the craniofacial mesenchyme is derived from neural crest cells, genes and molecular pathways regulating neural crest formation, migration, patterning, proliferation, and apoptosis, are all important for craniofacial development. Various aspects of cranial neural crest development and the roles of neural crest in craniofacial development have been reviewed recently by others (e.g., Wilkie and Morris-Kay, 2001;Chambers and McGonnell, 2002;Basch et al, 2004;Cox, 2004;Huang and Saint-Jeannet, 2004;Graham et al, 2004;Kulesa et al, 2004;Marazita and Mooney, 2004;Helms et al, 2005). We will focus on discussing the genes and molecular pathways critical for upper lip morphogenesis after the five facial prominences have formed.…”
Section: Genes and Molecular Pathways Critical For Upper Lip Developmentmentioning
confidence: 99%